OP0044 Abatacept Reduces CD4 Positive T-Cells in Psoriatic Arthritis Synovial Tissue; Preliminary Analysis from a Single Centre, Placebo-Controlled, Crossover Study. (9th June 2015) - Szentpetery, A.; McCormack, J.; Mellerick, L.; Heffernan, E.; Fabre, A.; FitzGerald, O.
Abstract : Background: Abatacept is a fully human fusion protein which selectively inhibits T-cell activation via the CD80/CD86:CD28 co-stimulation pathway and decreases serum levels of inflammatory cytokines and proteins implicated in the pathogenesis of psoriatic arthritis (PsA). Improvement in skin psoriasis with greatest reduction in PASI using 3 mg/kg dose of abatacept and reduction of clinical symptoms of PsA on 10 mg/kg dose has been previously shown. Data is limited on the immunopathological effect of abatacept in PsA synovial tissue. Objectives: (1) to study the change in immunohistochemical markers of synovial inflammation from baseline to 6 months after introducing abatacept treatment in patients with active PsA; (2) to evaluate the impact of a short period of abatacept 3 mg/kg treatment on both skin and joint-related clinical outcomes compared to placebo (PBO); (3) to investigate if cell markers of synovial inflammation correlate to disease activity measures and MRI synovitis scores. Methods: Biological treatment-naïve PsA patients with active disease for ≥3 months with clinical synovitis of a knee and the presence of a psoriatic skin lesion were enrolled. Patients were randomised to receive abatacept 3mg/kg or PBO infusion on day 1, 15 and 29; thereafter abatacept 10mg/kg was administered every 28 days for 5 months. Clinical data were collected at each visit. Ga-enhanced MRI and arthroscopic synovial biopsy of the involved knee were obtained at 0, 2 and 6 months. Immunohistological staining for CD3, CD4, CD8, FoxP3 and CD31 was performed and expression was scored on a 5 point scale using a semi-quantitative method [1]. FoxP3 (%/300 cells) and CD31 expression (number of positive vessels/10 HPF) was evaluated. The PsAMRIS semi-quantitative method was used to score MRI scans by one consultant radiologist. A total synovitis score (MRS (0-12)) per knee was calculated [2]. Results: 15 patients (8 female/7 male) with mean age of 45 (±14.6) years were recruited. 4 were on methotrexate, the remainder had not received any prior DMARDs. 73% and 80% of patients were EULAR responders at 2 and 6 months. Non responders had significantly higher CRP at basleline; ESR, CRP, DAS28 ESR and DAS28 CRP at 2 months and higher enthesitis scores at 6 months compared to responders. Preliminary synovial tissue analysis of the first 10 patients who completed the study revealed a reduction in expression for all cell markers as early as 2 months following treatment. There was a significant reduction in synovial CD4 expression at 6 months (p=0.038). Disease activity measures and cell markers did not show a significant difference between the treatment and PBO groups. MRS at baseline was lower (p=0.02) and change in DAS28 ESR 0 to 6 months was greater in the PBO group (p=0.08). Baseline DAS28 ESR significantly correlated with CD3, CD4 and FoxP3 expression at 6 months (rho=0.89 p=0.04). Conclusions: Abatacept reduced synovial CD4 positive T-cell expression in psoriatic arthritis over 6 months. DAS28 ESR at baseline correlated with all observed T-cell markers in the synovium 6 months following treatment. References: Tak PP et al. Arthritis Rheum 1997;40:217-225 Rhodes LA et al. Rheumatology 2005;44:1569-73 Disclosure of Interest: A. Szentpetery: None declared, J. McCormack: None declared, L. Mellerick: None declared, E. Heffernan: None declared, A. Fabre: None declared, O. FitzGerald Grant/research support from: Pfizer, AbbVie, BMS, MSD, Roche, UCB, Consultant for: Pfizer, AbbVie, BMS, MSD, Janssen, Roche, Speakers bureau: Pfizer, AbbVie, Janssen, Roche, UCB